Under Control? Or Border (as) Conflict: Reflections on the European Border Regime - Hess, Sabine (2017)
The migrations of 2015 have led to a temporary destabilization of the European border and migration regime. In this contribution, we trace the process of destabilization to its various origins, which we locate around the year 2011, and offer a preliminary assessment of the attempts at re-stabilization. We employ the notion of “border (as) conflict” to emphasize that crisis and exception lies at the very core of the European border and migration regime and its four main dimensions of externalization, techno-scientific borders, an internal mobility regime for asylum seekers, and humanitarization.